B cell receptor repertoire reconstitution in patients with neuromyelitis optica spectrum disorder receiving B-cell depletion therapy - Kim, Hyo Jae; Shin, Wangyong; Seo, Dayoung; Jang, Inhye; Ryu, Jihong; Choi, Lynkyung; Kim, Jinhee; Kim, Hyunjin; Lim, Young-Min; Lee, Eun-Jae (Frontiers in Immunology, 2025)
BackgroundNeuromyelitis optica spectrum disorder (NMOSD), driven by AQP4-IgG-producing B cells, is effectively managed with B cell depletion therapy (BCDT), such as rituximab (RTX). Although BCDT may reset the B cell compartment, its effects on B cell receptor (BCR) repertoire, clonality, isotype distribution, and somatic hypermutation (SHM) remain poorly understood. To examine how BCDT alters BCR features by comparing BCR repertoires between patients with NMOSD treated with RTX and azathioprine (AZA).MethodsFrom a prospective cohort, we recruited patients with NMOSD, including those on AZA (n = 11) and those 6–12 months post-RTX treatment (n = 9). Immunoglobulin heavy-chain libraries were generated from peripheral blood mononuclear cells and sequenced using Illumina MiSeq (2 × 300 bp). BCR features analyzed included isotype frequencies, D50 diversity index, top 10% clone fraction, SHM rates, and IGHV and IGHJ gene usage.ResultsAge (median 50 years) and disability scores were similar between the groups. In the RTX group, the median time since the last infusion was 9 months. RTX treatment led to a naïve B cell-dominant profile, with significantly reduced IgG1–IgG4 levels and unchanged IgA levels. Clonality was reduced, especially within the IgG isotype. SHM frequency was similar between groups, with no significant differences observed across individual isotypes. RTX also resulted in marked depletion of IGHV3-23, IGHV3-11, and IGHV3-73, along with IgG subclass-specific reductions in IGHV1-18, IGHV1-3, IGHV1-46, IGHV1-69, and IGHJ4.ConclusionSix to twelve months after RTX treatment, patients with NMOSD display a rejuvenated BCR repertoire characterized by naïve B cell predominance, reduced class-switched clonality, and selective loss of V gene segments. These findings support the mechanism by which BCDT resets pathogenic memory B cells and offer benchmarks for monitoring B cell reconstitution in NMOSD.